THE EFFECT OF FINANCIAL RATIOS ON EARNINGS MANAGEMENT: A CASE STUDY OF HEALTH COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2021-2023 - Audy Herlina Puspitasari; Anik Yuliati (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This research aims to explore the influence of profitability, liquidity, and leverage on the practice of earnings management among healthcare companies publicly traded on the Indonesia Stock Exchange during the period of 2021 to 2023. Profitability is represented by Return on Assets (ROA), liquidity is indicated by the Current Ratio (CR), and leverage is measured using the Debt to Equity Ratio (DER). To assess earnings management, the study adopts the Modified Jones Model. A quantitative approach is utilized, relying on secondary data derived from the financial reports published by the Indonesia Stock Exchange. Utilizing purposive sampling, the study selects 48 financial reports from healthcare companies that satisfy the established criteria, drawn from a total population of 84 reports. Multiple regression analysis is performed via SPSS version 30 to process the data. Results indicate that neither profitability nor liquidity significantly impacts earnings management, while leverage demonstrates a positive and statistically significant influence on earnings management practices in the healthcare sector